Health Promotion and Prevalence Surveys Soil-Transmitted Helminths Infection in Jatiwarna, Bekasi City - Heru Setiawan; Husjain Djajaningrat (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2022)
Soil-transmitted helminths infection is still a serious health problem that mainly occurs in pre-school-aged children. In the context of tackling soil-transmitted helminths infection, we carried out a community service program through public health promotion and a survey on the prevalence of soil-transmitted helminths infection in preschool-aged children in Jatiwarna, Bekasi City. Health promotion is carried out by means of lectures, discussions, and distribution of pamphlets on soil-transmitted helminths infections. In addition, we distributed questionnaires to measure the level of knowledge, attitude and healthy living behavior in the community. There were 37 respondents who filled out the questionnaire. The prevalence survey was carried out by means of direct slide microscopic examination of the fecal samples of 30 preschool-school children. Questionnaire data showed that the majority (59.9 percent) of respondents had moderate knowledge about soil-transmitted helminths infection. Most of the respondents had a healthy attitude and behavior in the good category with a percentage of 45.9 percent and 89.2 percent, respectively. Meanwhile, the results of microscopic examination showed that the prevalence of soil-transmitted helminths infection in preschool-school-age children was 10 percent. It is necessary to administer mass anthelmintic drugs to children and promote health in the community on a regular basis and further research is needed to determine the prevalence and risk factors for soil-transmitted helminths infection in a wider population.